Gorham's Massive Osteolysis - A Rare Case Report - Mangala Meti; Neelkantrao Patil; Surekha Puranik (Wolters Kluwer Medknow Publications, 2006)
Massive osteolysis is well known by the synonyms vanishing bone disease, phantom bone disease. First case ever reported was by Jackson in 1838 and later in 1972 in a patient with disappearing humerus. Romer in 1924 reported first case in the jaws. There are only very few cases reported in the jaws in the literature. Considering the rarity of the condition, this case of massive osteolysis of entire mandibular involvement, in an Indian woman is the first ever case to be reported in the literature. Thus we report here an interesting case of vanishing bone disease of the lower jaw and a generalized wasting in a 60 year old female patient.The clinical and radiologic findings were consistent with the criteria for the diagnosis of Gorham's massive osteolysis.